Kant’s Aesthetic Essentiality as Exposed on Selena Gomez’s Who Says - Pasopati, Rommel Utungga; Firda, Erlis Hersetya; Ayu, Evangelin Rambu; Fahmi, Muhammad Abu Rijal; Salsabiyla, Raddine (CV. Tripe Konsultan, 2024)
Beauty for women is crucial as an intersection of their desires, needs, and satisfactions. Who Says is a song by Selena Gomez released in 2011 that inspires women to be confident since beauty is actually essential. Immanuel Kant’s aesthetic essentiality underlines that beauty is not agreeable since it relies on its own essence. Then, how may Kant’s aesthetic essentiality see the position of beauty in Selena Gomez’s Who Says? Through qualitative method on cultural studies, this article exposes Kant’s perspective and Gomez’s song. Recent various beauty standards make women feel insecure, but the song encourages girls to be who they are and not let what other people say get to them. All women should ignore forceful beauty standards because any expectation could be detrimental to women’s self-esteem. In conclusion, the song shows that beauty is essential and could only be experienced by individuals, not by any beauty standard.